2007
DOI: 10.1016/j.sab.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sediment pollution in the rivers of the Hungarian Upper Tisza Region using non-destructive analytical techniques

Abstract: The rivers in the Hungarian Upper Tisza Region are frequently polluted mainly due to mining activities in the catchment area. At the beginning of 2000, two major mining accidents occurred in the Romanian part of the catchment area due to the failure of a tailings dam releasing huge amounts of cyanide and heavy metals to the rivers. Surface sediment as well as water samples were collected at six sites in the years 2000-2003, from the northeast-Hungarian section of the Tisza, Szamos and Túr rivers. The sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
(34 reference statements)
1
10
0
1
Order By: Relevance
“…To date, many researchers have conducted extensive surveys of heavy metal contamination in sediments (Meybeck et al 2007;Osán et al 2007). The results demonstrated that accumulation of heavy metals has occurred in sediments of different regions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many researchers have conducted extensive surveys of heavy metal contamination in sediments (Meybeck et al 2007;Osán et al 2007). The results demonstrated that accumulation of heavy metals has occurred in sediments of different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the cyanide and heavy metal spill from Baia Mare in January 2000, it was recently the most serious environmental disaster in Tisza river (Laszlo et al 2000;WWF 2002). In other studies (Laszlo et al 2000;Fleit and Lakatos 2003;Osan et al 2002Osan et al , 2007, high concentrations of these elements were also noticed in 10-cm surface sediment layers of Tivadar village, as well as the upper Tisza, as indications of these newly arrived pollution events. For the peaks occurring at a depth of about 120 cm of the core, the most possible explanation is heavy runoff from historical metal exploitation.…”
Section: Vertical Variation Of Heavy Metals In Sediment Of Kiss Janosmentioning
confidence: 62%
“…The upper Tisza river, flowing through Hungary, has been subject to severe metal pollution due to mining activities and major industrial complexes in Romania, near the border of Romania and Hungary. Heavy floods, which occur regularly due to snow-melting and intensive precipitation, are a great potential risk of enhancing these metal pollutions by leaching of the mine tailing, which are stocked nearby the river banks, as well as spreading of the contamination outside the river bed and further downstream (Hamar and Sarkany-Kiss 1999, Osan et al 2002, 2007. The river has about 70 oxbow lakes, with surface areas larger than 5 ha, that are only connected to the main river during flooding events (Braun et al 2000).…”
mentioning
confidence: 99%
“…The TXRF technique is mainly used for micro-and trace-element analysis of evaporated solvents, aerosols and powders [27,28]. Another common application is the control of surfaces' contamination [29].…”
Section: Total Reflection X-ray Fluorescencementioning
confidence: 99%